Poverty, Food Security and Malnutrition in an Urban and Rural Setting: Case of the former West Kordofan State: ملخص رسالة دكتوراة الفلسفة في العلوم الأسرية بعنوان : الفقر ، الأمن الغذائي وسوء التغذية حالة ولاية غرب كردفان (سابقاًُ) - Ibrahim, Hashim Suliman (Journal of Faculty of Education, 2021)
Food security is a situation that exists when all people at all times have physical access to sufficiency safe and nutritious food for a healthy and active life ( FAO, 1996 ). Food availability and access to it are two essential determinants of food security, however , the former does not ensure the later as food may be available nationally or locally but is not accessible to all households ( Braune, 1993 ) . Sudan, the largest country in Africa (2.5 million km2) has diversified ecological zones and is known for its rich agricultural potentials, its under-fished waters (rivers and Red Sea Coast) and livestock raised on natural pastures. Because of this immense potential as a food producer to satisfy local demand and export the excess it was declared by the government in the 1970s as the "World Food Basket".(Salih private communication) Food intake is a major component for achieving optimum nutritional status hence inadequate intake can lead to under nutrition. In developing countries under nutrition is mostly due to inadequate intake of energy and protein ( Latham,1997). Nearly most studies on nutritional status were aimd at the under five children as representative of the household. This study will involve the nutritional status of the whole household to reach abetter understanding of the relationship between food and nutrition security The investigation was carried out in Al Nuhud town representing an urban area and six surrounding villages representing the rural area.